2021
DOI: 10.17306/j.afs.0892
|View full text |Cite
|
Sign up to set email alerts
|

Talinum paniculatum (Jacq.) Gaertn. leaves – source of nutrients, antioxidant and antibacterial potentials

Abstract: Background. The diet of most of the population is limited to a reduced number of plants, even in areas that have a varied and extensive diversity, such as Brazil. Unconventional Food Plants (UFPs) are plants considered exotic, native, and wild that grow naturally and can be used as food. Among these is Talinum paniculatum (Jacq.) Gaertn., which is widespread throughout Brazil and can be a potential source of nutrients. Due to the potential of utilization of UFPs in human food and the lack of studies regarding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
0
5
0
3
Order By: Relevance
“…Desde as folhas, pecíolos, frutos, flores, botões florais, caule, haste e raízes caracterizados apresentaram um elevado teor de umidade, na faixa de 94,16% a 65,91% (Tabela 1). Porém, no estudo realizado por Menezes et al, (2021) o valor apresentado para o percentual de umidade está equivocado. De acordo com a metodologia descrita pela Association of Official Analytical Chemists, utilizada no estudo, o teor de umidade é expresso em matéria úmida e não em matéria seca, como está descrito no trabalho.…”
Section: Composição Centesimalunclassified
“…Desde as folhas, pecíolos, frutos, flores, botões florais, caule, haste e raízes caracterizados apresentaram um elevado teor de umidade, na faixa de 94,16% a 65,91% (Tabela 1). Porém, no estudo realizado por Menezes et al, (2021) o valor apresentado para o percentual de umidade está equivocado. De acordo com a metodologia descrita pela Association of Official Analytical Chemists, utilizada no estudo, o teor de umidade é expresso em matéria úmida e não em matéria seca, como está descrito no trabalho.…”
Section: Composição Centesimalunclassified
“…The results of this study are supported by Kim et al on 2010, who have proven that the administration of ginseng extract could increase intracellular activities of the SOD enzyme (7) . Meanwhile, Menezes et al on 2021 suggest that Javanese ginseng extract potentially has antioxidants to counteract free radicals and superoxide radicals (8) . Other studies have also revealed that Javanese ginseng contains secondary metabolites, such as saponins, flavonoids, and tannins.…”
Section: P a G E |mentioning
confidence: 99%
“…There has been researched by Kim et al on 2010, who have proven that the administration of Korean red ginseng extract can increase intracellular SOD enzyme activity 7 , and research by Menezes et al on 2021, showed that ginseng leaves extract has the potential to have antioxidants to counteract free radicals and superoxide radicals 8 . These two studies only analyzed the effect of ginseng on antioxidant potential in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…The root is known to possess a tonic effect, and believed to have benefits to the body system (Santoso et al, 2016;Sulistiono et al, 2017). Ginseng leaves contain protein, magnesium, potassium, ascorbic acid, phenonugrlic, flavonoids, and iron, which provide beneficial effects (Moura et al, 2020;Menezes et al, 2021). The use of medicinal herbs or traditional medicine is assumed to be safe, but potential toxicity might occur, either at a low or high dose, during longterm usage.…”
Section: Introductionmentioning
confidence: 99%